"Asset stripping" the declining mental hospital. Issue 6207 (12th January 1980) - Fottrell, E; Spy, T; Mearns, G; MacLean, I; Fogarty, M
Abstract : A psychogeriatric day hospital was developed from a long-stay back ward of a large mental hospital whose population of patients had decreased by half. Women in the 70-80 age group with varying degrees of dementia benefited most from such facilities. In view of the current cut-back in Government spending one of the greatest assets in providing a comprehensive service for the elderly mentally infirm may well be found in the declining mental hospital.